Mengintegrasikan Kecerdasan Buatan Dalam Pendidikan Tinggi: Kajian Literatur Tentang Peran AI Dalam Pembelajaran Mahasiswa - Darmawati; Nurhafizah (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
The development of artificial intelligence (AI) technology has significantly impacted various sectors, including higher education. This study aims to analyze the role of AI in enhancing the quality of student learning through a literature review approach. The findings reveal that AI offers numerous benefits, such as personalized learning, increased accessibility, and efficiency in assessments and administration. AI enables the delivery of tailored instructional materials, provides immediate feedback, and supports students from diverse backgrounds to access equitable learning opportunities. However, AI implementation also faces challenges, including technological gaps, lack of user skills, and resistance to change. Additionally, ethical issues related to data privacy and security require special attention. This study concludes that despite these challenges, AI has great potential to improve the quality of higher education inclusively and efficiently. Policy recommendations include enhancing technological infrastructure, providing training for users, and developing regulations to ensure responsible AI implementation in education.